B cell phenotypes and antibody signatures associate with interpatient variation in the lung adenocarcinoma tumor microenvironment - Rasche, Kamille M.; Tieri, David; Morrissey, Samantha M.; Li, Hong; Zhang, Fan; Gibson, William S.; Ford, Easton E.; Jana, Uddalok; Smith, Melissa L.; Yan, Jun; Watson, Corey T. (Frontiers in Immunology, 2026)
IntroductionNon-small cell lung cancer is the leading cause of cancer-related mortality worldwide, with lung adenocarcinoma (LUAD) as the most common subtype. Although early-stage disease is often treated surgically, advanced LUAD typically requires chemotherapy, radiation, and/or immunotherapy, largely focused on T cell–mediated responses. Therapeutic efficacy, however, is also shaped by tumor-infiltrating (TI) B cells, whose roles in LUAD remain incompletely understood.MethodsWe performed cytometry by time of flight (CyTOF) using 44 markers on matched tumor, adjacent lung, and peripheral blood samples from 48 LUAD patients to define TI immune landscapes. 66 immune cell subsets were identified, and patients were stratified into four groups based on TI cell composition. Adaptive immune receptor repertoire sequencing (AIRR-seq) of IgM and IgG was conducted on matched samples from 29 patients to assess clonal expansion and affinity maturation. Subisotype-resolved AIRR-seq was additionally performed on tumor samples from 18 patients.ResultsCyTOF analysis revealed four patient groups with distinct TI immune profiles. AIRR-seq demonstrated increased clonal expansion and affinity maturation in tumors compared to adjacent lung and blood. Tumor-specific IGHV enrichment patterns were observed but were not associated with patient group assignment. Instead, clonal expansion was greatest in tumors with higher lymphocyte proportions. Subisotype-resolved analysis showed enrichment of IGHG2 and IGHG3 in tumors from patients with low TI B cell abundance, whereas IGHG4 was enriched in patients with high TI B cell infiltration and correlated with four CyTOF-defined immune subsets.DiscussionThese findings reveal substantial inter-individual variation in TI immune landscapes and highlight distinct B cell repertoire and subisotype features within LUAD tumors. Together, these data suggest that B cell composition and antibody subisotype usage may contribute to immune contexture and could inform the development of more tailored immunotherapeutic strategies in LUAD.